FPGAs versus GPUs in Data centers - Falsafi, Babak; Dally, Bill; Singh, Desh; Chiou, Derek; Yi, Joshua J.; Sendag, Resit (IEEE MICRO, 2017)
This article presents position statements and a question-and-answer session by panelists at the Fourth Workshop on Computer Architecture Research Directions. The subject of the debate was the use of field-programmable gate arrays versus GPUs in datacenters.